Complexity in Engineering Design Education: Decision-Making, Framing, and Collaboration - Batrouny, Nicole. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Kristen Wendell.; Committee: Brian Gravel, Trevion Henderson, and Shanna Daly.; Keywords: Mechanical engineering, and Education.